(3JQLeI GdTjN CHj GdMSf Ydi GdJejei GdTTJQis
(3ChdgG (B:s
(3GdMeO ddg hMOg s
(3BNQgG (B:s
(3HjGf ef GdRLd GdTTJQi s
(3Vef eLehY , JQJjHgG (B: (3ef U (B133 - (3U(B141s
(3fbdkG Yf eNJUQ TQM GdfUjMI GdcGajIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B1 - (3U (B91 s
(3eUOQ GbJfGA GdCUd (B:s
(3GdHdOjI HGdCScfOQjI (B(3024(16)) s
Keywords: (3GdJGQjNs